Is CSR the new competitive environment for CEOs? The association between CEO turnover, corporate social responsibility and board gender diversity: Asian evidence. (3rd January 2021) - Orij, René P.; Rehman, Saif; Khan, Hashim; Khan, Faisal
Abstract: The choice for corporate social responsibility (CSR) as a strategic tool remains a debatable issue. While past studies suggest that the financial performance of a firm is the primary driver of CEO turnover; we found that a firm's CSR performance also has a relationship with CEO turnover, a negative relationship. Consistent with the hypotheses, our findings suggest that firm's CSR performance positively moderates the firm's financial performance–CEO turnover relationship. The firm's negative CSR performance–CEO turnover relationship is more pronounced in highCSR‐ranked firms. Precisely, the findings posit that CSR appears to (a) reduce likelihood of CEO turnover in general, (b) somewhat increases the likelihood of CEO turnover in case of poor financial performance, and (c) greatly reduces the likelihood of CEO turnover in case of better financial performance is good. Therefore, a CEO who is motivated to deliver profits in a socially responsible way may face both positive and negative personal consequences. Given the importance of the board gender diversity/gender critical mass, our findings show that the presence of gender critical mass moderates the firm's negative performance (CSR and ROA)–CEO turnover relationship. Further, we split the sample into low and highCSR‐ranked firms, and the findings show that the presence of gender critical mass substitutes the firm's negative performance (CSR and ROA)–CEO turnover relation in highCSR‐ranked firms; whereas, it moderates the relation in lowCSR‐ranked firms. Therefore, the presence of gender critical mass supports the statement that "CSR—combined with board gender diversity—is the new competitive environment for CEOs."